Phenotyping for genetic divergence under transplanted and low-cost direct-seeded rice (Oryza sativa) production systems - KHOKHAR, J S; SARIAL, A K (The Indian Journal of Agricultural Sciences, 2016)
A set of 25 rice (Oryza sativa L.) genotypes belonging to different maturity groups and genetic background (Basmati, non-Basmati and hybrids) were phenotyped in two experiments at the experimental farm of the Rice Research Station, CCS Haryana Agricultural University, Kaul during kharif season (June-November) 2012. The experiments consisted of direct seeded and transplanted production systems in RBD with three replications each. The plot size was kept at 2× 0.20 × 5 m2. The data were recorded on 5 randomly selected plants per genotype per replication for 12 traits, viz. grain yield (GY), days to flowering (DTF), days to maturity (DTM), plant height (PHT), effective tillers/ plant (T/PT), percent filled spikelets (FSPK), test weight (TWT), biological yield/plant (BYD), harvest index (HI), hulling per cent (H%), milling per cent (M%), and head rice recovery (HRR). The analysis of variance revealed significant differences among the genotypes for all the characters. The genetic dissimilarities measurement using generalized Mahalanobis distance (D2) indicated that the genotypes with greater dissimilarity were different under high cost transplanted (TPR) than those under low cost direct seeded rice (DSR) production system. Similarly, the range of D2 values and the most divergent clusters were different in two production systems. Although genotypes were grouped into 6 clusters under both the systems, yet their members were different. Plant height showed maximum (18.67%) contribution towards divergence under low cost while DTF (29.67%) under high cost. Accordingly, genotypes were identified and recommended for evaluation in large trials and for hybridization for trait wise improvement for direct seeded production system. The results obtained thus have great relevance to the future rice improvement programme.